Exploring the impact of orthodontic appliances on the oral microbiome and inflammatory parameters - Michael Nemec; Patrick Ringl; Kathrin Spettel; Lisa Schneider; Richard Kriz; Sonia Galazka; Marcus Sedlak; Erwin Jonke; Oleh Andrukhov; Athanasios Makristathis (Progress in Orthodontics)
Abstract Background The symbiotic relationship between the oral microbiome and the host immune system is a prerequisite of oral health. Disruptions to this system can be associated with the development of diseases like dental caries. Introducing orthodontic treatments, such as aligners and fixed appliances, might impact this microbial ecosystem. This study evaluated potential changes in salivary microbiome and the level of inflammatory marker myeloid-related protein 8/14 in patients undergoing orthodontic treatment with aligners or fixed appliances. Methods Forty-eight patients were divided into two groups for treatment with fixed appliances or clear aligners. Unstimulated saliva samples were collected at baseline, three, and six months for microbiome analysis via 16 S rRNA sequencing and MRP-8/14 level measurement using ELISA. Results Among 503 identified microbial species, no significant changes were noted in overall microbiome. A considerable increase of caries-relevant species could not be observed either. MRP-8/14 levels remained unchanged across treatments, indicating no alterations in the inflammatory level. Conclusion Orthodontic treatment with fixed or removable appliances does not significantly alter the salivary microbiome or influence inflammation, suggesting that these interventions are unlikely to affect oral health negatively.